Ethnobotanical Survey and Cercaricidal Activity Screening of Medicinal Plants Used for Schistosomiasis Treatment in Atwima-Nwabiagya District, Ashanti Region, Ghana - Evelyn Asante-Kwatia; Lord Gyimah; Arnold Donkor Forkuo; William Kofi Anyan; Makafui Adzo Gbemu; Francis Ackah Armah; Abraham Yeboah Mensah (Journal of Parasitology Research)
This study focused on documenting and evaluating the cercaricidal activity of medicinal plants used for schistosomiasis treatment in an endemic area in Ghana. Through semistructured questionnaires, personal interviews with herbalists in communities surrounding the Barekese dam in the Atwima-Nwabiagya district, where the disease is endemic, were carried out. Thirty medicinal plants distributed in 19 families were reported to be used for schistosomiasis treatment in the survey. Information on the plants, including scientific names, common names, families, and the used plant part were recorded. The families Apocynaceae and Euphorbiaceae recorded the highest number of plants (14% each), followed by Asteraceae (10%), Loranthaceae (7%), and Rubiaceae (7%). In vitro cercaricidal activity of methanol extracts of nine out of the thirty plants was performed by exposing human Schistosoma mansoni cercariae obtained from Biomphalaria pfeifferi to various concentrations of extracts over a duration of 240 minutes. All the plants tested demonstrated time- and concentration-dependent cercaricidal activity. With lethality being set at <1000 μg/mL, the cercaricidal activity in order of decreasing potency was as follows: Withania somnifera (LC50 = 1.29) > Balanites aegyptiaca (LC50 = 7.1) > Xylia evansii (LC50 = 11.14) > Jathropha multifida (LC50 = 12.9) > Justicia flava (LC50 = 22.9) > Anopyxis klaineana (LC50 = 182.81) > Ximenia americana (LC50 = 194.98) > Loranthus lecardii (LC50 = 223.87) > Bridelia tenufolia (LC50 = 309.03) > Zanthoxylium zanthoxyloides (LC50 = 851.94). Phytochemicals, including alkaloids, tannins, triterpenes, saponins, phytosterols, and flavonoids were identified in the plants. The result of this study gives scientific credence to the traditional use of these plants in the treatment of schistosomiasis and proves that the rich botanical knowledge of medicinal plants provides an incredible starting point for the discovery of new anti-schistosomal drugs for the local population.